2009
DOI: 10.1002/ijc.24847
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin regulates expression of VEGF and tumorigenesis in human colon cancer

Abstract: Tristetraprolin (TTP) is an AU‐rich element‐binding protein that regulates mRNA stability. Here, we report that TTP suppress the growth of human colon cancer cells both in vivo and in vitro by regulating of the expression of vascular endothelial growth factor (VEGF). TTP protein expression in human colonic tissues was markedly decreased in colonic adenocarcinoma compared with in normal mucosa and adenoma. VEGF expression was higher in colonic adenocarcinoma than in normal mucosa and adenoma. Specific inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 40 publications
(50 reference statements)
8
91
0
3
Order By: Relevance
“…Cell Lines-Previously, we prepared Colo320/TTP, a stable transfectant derivative of Colo320 that overexpresses TTP, and reported that VEGF expression was reduced by overexpression of TTP (32). While we were searching for genes with expression levels changed by TTP overexpression, we found that the LATS2 expression level was also reduced in Colo320/TTP cells compared with that in Colo320 cells (Fig.…”
Section: Lats2 Expression Is Inversely Correlated With Ttp Expressionmentioning
confidence: 93%
See 2 more Smart Citations
“…Cell Lines-Previously, we prepared Colo320/TTP, a stable transfectant derivative of Colo320 that overexpresses TTP, and reported that VEGF expression was reduced by overexpression of TTP (32). While we were searching for genes with expression levels changed by TTP overexpression, we found that the LATS2 expression level was also reduced in Colo320/TTP cells compared with that in Colo320 cells (Fig.…”
Section: Lats2 Expression Is Inversely Correlated With Ttp Expressionmentioning
confidence: 93%
“…Colo320/pcDNA and Colo320/TTP cells, stably transfected with pcDNA4.1 and pcDNA-TTP, respectively, were prepared as described previously (32). A549, Colo320, Colo320/pcDNA, and Colo320/TTP cells were cultured in RPMI 1640 medium, and 293-EBNA, NT2, HepG2, and PA1 cells were cultured in Dulbecco's modified Eagle's medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TTP expression is significantly decreased in various cancers (Brennan et al, 2009), and this down-regulation correlates with increased expression of proto-oncogenes (Lee et al, 2010a;Young et al, 2009). The low level of TTP in cancer cells may not be sufficient to inhibit IL-23 expression, resulting in high IL-23 levels in cancer cells (Kesselring et al, 2010;Langowski et al, 2006;Martin-Orozco et al, 2009) which in turn may support tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…The AREs may destabilize inflammatory signaling mRNAs through specific binding of proteins that promote mRNA degradation (Caput et al, 1986;Shyu and Wilkinson 2000). Tristetraprolin (TTP) is a well-characterized ARE-binding protein that is involved in posttranscriptional regulation of inflammatory cytokines, proto-oncogenes, and growth regulatory genes (Cha et al, 2011;Lee et al, 2010a;2012;2013). TTP-knockout mice develop severe inflammatory arthritis and autoimmune dysfunction, indicating a role of TTP in limiting the inflammatory response (Taylor et al, 1996).…”
Section: Introductionmentioning
confidence: 99%